2023
DOI: 10.1111/cas.16036
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell‐derived exosomal miR‐20a‐5p inhibits CD8+ T‐cell function and confers anti‐programmed cell death 1 therapy resistance in triple‐negative breast cancer

Weina Li,
Guohui Han,
Feng Li
et al.

Abstract: Circulating miRNAs (cirmiRNAs) can be packaged into the exosomes, participating in intercellular communication, which affects the malignant progression and therapy resistance of triple‐negative breast cancer (TNBC). Currently, immune checkpoint inhibitors that regulate T‐cell function, especially antibodies against programmed cell death 1 (PD‐1) or its ligand PD‐L1, are emerging as new promising therapy for TNBC patients. However, only very limited patients showed complete or partial response to anti‐PD‐1 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Some studies have found that circulating miR-20a-5p released by TNBC cells through exosomes promotes cancer cell growth by inducing cluster of differentiation 8 (CD8 + ) T cell dysfunction, leading to immunosuppression. Modulating miR-20a-5p could emerge as a novel approach to overcome the resistance of TNBC to anti-PD-1 immunotherapy ( 37 ).…”
Section: Exosomes Influence Tumor Developmentmentioning
confidence: 99%
“…Some studies have found that circulating miR-20a-5p released by TNBC cells through exosomes promotes cancer cell growth by inducing cluster of differentiation 8 (CD8 + ) T cell dysfunction, leading to immunosuppression. Modulating miR-20a-5p could emerge as a novel approach to overcome the resistance of TNBC to anti-PD-1 immunotherapy ( 37 ).…”
Section: Exosomes Influence Tumor Developmentmentioning
confidence: 99%
“…Exosomal miR-20a-5p is released by breast cancer cells and transferred to CD8 + T cells, where it inhibits their function by targeting the nuclear protein coactivator of histone transcription (NPAT) ( 347 ). NPAT is a cell cycle gene highly expressed in immature CD8 T cells, The miR-20a-5p binds to the 3’-UTR of NPAT, inducing the development of resistance to anti-PD-1 therapy.…”
Section: Tumor Cell-derived Exosomes (Tex) In Cancer Therapymentioning
confidence: 99%
“…NPAT is a cell cycle gene highly expressed in immature CD8 T cells, The miR-20a-5p binds to the 3’-UTR of NPAT, inducing the development of resistance to anti-PD-1 therapy. These findings suggest that exosomal miR-20a-5p derived from triple-negative breast cancer plays an important role in promoting immune escape and immunotherapy resistance by inducing CD8 + T cell dysfunction ( 347 ). Breast cancer-derived exosomes containing tumor cell-derived PD-L1 interact with PD-1-producing T cells to significantly reduce responses to immune checkpoint blockade agents.…”
Section: Tumor Cell-derived Exosomes (Tex) In Cancer Therapymentioning
confidence: 99%